Towards A Juristocratic State: A Critical Analysis Of The Constitutional Court Decision No 90/Puu-Xxi/2023 Concerning The Age Limits Of Vice Presidential Candidates - Dian Pratama, Alip; Flambonita, Suci; Rumesten RS, Iza; Rasyid, Muhamad; Yunithia Putri, Taufani (Fakultas Hukum Universitas Lampung, 2024)
The Constitutional Court Decision Number 90/PUU-XXI/2023 Concerning the Age Limit for Vice Presidential Candidates in the 2024 Presidential Election has caused much controversy, both politically and legally. This decision has profound implications for Indonesia’ political configuration, as it grants constitutional legitimacy to Gibran Rakabuming Raka, enabling him to run as a candidate for vice president of the Republic of Indonesia in the 2024 General Election. In the context of the legal debate, several problems have emerged, including the impact of this decision on the quality of democracy in Indonesia. One key concern is whether this decision is the initial gateway for Indonesia to enter a system called 'juristocracy'. This term refers to a situation where the Constitutional Court Decision justifies the practice of 'negative legislation', where the legislative function is constitutionally only given to the President and the DPR, but the Constitutional Court, through its 'final and binding' decision power, makes this a loophole that potentially damage democracy. This research is focused on examining the decision based on the two fundamental problems outlined above, using a library research method based on normative research, with a conceptual approach as its foundation. The analysis employs the theory of the rule of law to critically assess whether the decision has significant positive or negative implications for the sustainability of democracy and the existence of the rule of law in Indonesia in the future.